THE EVALUATION OF STRATEGIC COMMUNICATION UTILIZATION OF MOBILE PHONE CAMPAIGN FOR TIDAL FLOOD DISASTER MANAGEMENT IN NORTH JAKARTA - Ainurizaq Putri Aria Santi; Agus Naryoso, S.Sos, M.Si (Interaksi Online, 2017)
Indonesia is an archipelago country which located in ring of fire zone. It means, the potency of natural disaster is huge in this region. Flood is one of the most common disaster that happen in Indonesia, especially in DKI Jakarta province. Based on data from WHO, flood that happen in February 2007 and hit 80 districts in Jakarta caused traffic chaos and disabling the city. More than 73.000 houses flooded with 10 cm untill 5 m water level. This research aim to doing evaluation towards strategic communication that conducted by the official of Ministry of Communication and Information Technology Republic of Indonesia in terms of utilization of mobile phone campaign for tidal flood disaster management in North Jakarta. This research using descriptive qualitative method with case study approach. This research using Information Processing Theory Mc Guire, Systematic-Heuristic Model, and Ellaboration Likelihood Model. This research was conducted with six informants, consist of two informants that comes from Ministry of Communication and Information Technology, two informants from local people in North Jakarta, one informant from BMKG (Meteorological, Climatological, and Geophysical Agency) and one informant from BPBD (Regional Board for Disaster Management). The result of this research is strategic communication since planning until evaluating of the campaign is very important to do, to achieve the goals. While conducting mobile phone campaign, Ministry of Communication and Information Technology was doing analysis, set the standards and targets, set the strategy and tactics, time allocation, resources, and also doing evaluation.